Anomalies of the systemic venous system - Özme, Şencan; Akçoral, Adnan; Bilgiç, Arman; Olguntürk, Rana; Ekici, Enver (The Turkish Journal of Pediatrics, 1980)
Eighty-seven subjects with anomalies of systemic venous return were studied in detail. Angiography was used for the detection and the evaluation.The patients were between 3 and 20 years of age. Twenty nine subjects had persistence of the left superior vena cava with congenital cardiac defects. Four subjects had left superior vena cava connected to the left atrium. Left superior vena cava drained into the right atrium in the remaining twenty-six subjects. The inferior vena cava was absent in twenty-four subjects. One subject had left vena cava inferior instead of the right vena cava without situs inversus. Four subjects were diagnosed as having absence of the superior vena cava. Only one patient had sub and supra cardinal veins.It was emphasized that special attention should be given for the detection of these anomalies because they may be present an important problem during cardiac surgery and in the differential diagnosis of mediastinal masses.